Supporting survivors of campus dating and sexual violence during COVID-19: A social work perspective. (2nd January 2021) - Bennett, Esther R.; Snyder, S.; Cusano, J.; McMahon, S.; Zijdel, M.; Camerer, K.; Howley, C.
ABSTRACT: The issue of dating and sexual violence (DSV) on college campuses has received increased attention nationwide as a criminal justice and public health issue. College and university employed social workers play a critical role in preventing and responding to campus DSV through direct clinical services to students as well as prevention through educational programming and training. COVID-19 has negative implications for DSV student victims, as well as service delivery and accessibility. This paper examines the innovative methods used by university employed social work clinicians and educators to meet evolving mental health care needs and continue violence prevention services during COVID-19.